1980
DOI: 10.1084/jem.151.2.486
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to in vitro tolerance induction of adult B cells from mice with an X-linked B-cell defect.

Abstract: C B A / N mice, a m u t a n t subline of the C B A / C a strain, have an X-linked B l y m p h o c y t e -i m m u n e defect. These mice and F1 male progeny derived from C B A / N females fail to produce specific a n t i b o d y after i m m u n i z a t i o n with certain thymicindependent (TI) antigens (1-4). In addition, these mice fail to produce I g M or IgG responses to either the T I or T -d e p e n d e n t derivatives of the hapten phosphorylcholine (PC) (5, 6). Moreover, analysis of surface m e m b r a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

1981
1981
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 14 publications
1
19
0
Order By: Relevance
“…In many ways, XID B cell responses resemble those of newborn mice (67). For example, anti-IgM-induced B cell proliferation can be restored in both age groups by second signals such as LPS, IL-4, CD40L, or CpG (53,54,(68)(69)(70).…”
Section: Discussionmentioning
confidence: 99%
“…In many ways, XID B cell responses resemble those of newborn mice (67). For example, anti-IgM-induced B cell proliferation can be restored in both age groups by second signals such as LPS, IL-4, CD40L, or CpG (53,54,(68)(69)(70).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, whereas in normal and conventional mice, <10% of splenic B cells are tolerance susceptible in vitro, >50% of splenic B cells in F~ male defective mice remain tolerance susceptible (26). Since PC is a ubiquitous environmental antigen, it is an interesting possibility that the absence of mature PC-specific B cells in (CBA/N × BALB/c)FI male defective mice is the result of tolerance induction by a normal environmental antigen.…”
Section: Response To Pc Of Cells Derived From Mice That Were Neonatalmentioning
confidence: 99%
“…Previous studies from several laboratories (17)(18)(19)(20)(26)(27)(28) have demonstrated a multifaceted sex-linked immunologic deficiency in CBA/N mice and F1 male mice derived from a CBA/N parent. One of the deficiencies of these mice is an almost total absence, from the primary B cell repertoire, of cells that can respond to PC, even presented on highly immunogenic carriers (17)(18)(19)(20).…”
Section: Response To Pc Of Cells Derived From Mice That Were Neonatalmentioning
confidence: 99%
See 2 more Smart Citations